Simulation of Protocol for Initiation of Communication Sessions using dynPLA Model - Pranevicius, H.; Paulauskaite–Taraseviciene, A.; Jarutis, A. (Elektronika ir Elektrotechnika, 2010)
In the paper, Session Initiation Protocol (SIP) formal model was created using dynamic PLA (dynPLA). The considered problem was presented as the system with changing structure in which both occurrence and removal of the communication sessions causes changes in the system’s structure. The simulation was used to study the algorithms applied for establishment of communication sessions and their influence on signaling parameters, such as the duration of connection, the message loss, and more. The obtained simulation results allow the requirements on server’s technical characteristics be based upon given connection session intensity. The presented methodology can be extended considering more complex cases when users are on different networks.